2022
DOI: 10.1055/a-1811-9407
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-assisted staging in Barrett’s carcinoma

Abstract: Background and study aims: Artificial intelligence (AI) is increasingly being used to detect neoplasia and interpret endoscopic images. The T stage of Barrett’s carcinoma is a major criterion for deciding on subsequent treatment. Although endoscopic ultrasound is still the standard for preoperative staging, its value is debatable. Novel tools are required to assist with staging, to optimize results. This study aimed to investigate correctly identified T stages of Barrett’s carcinoma using an artificial intelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“… 34 In 2022, Knabe et al . 35 used AI to assess the tumor (T) staging of adenocarcinoma in BE in 1020 images. They were able to identify mucosal cancer with accuracy of 68% and larger T3/T4 lesions with accuracy of 73%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 34 In 2022, Knabe et al . 35 used AI to assess the tumor (T) staging of adenocarcinoma in BE in 1020 images. They were able to identify mucosal cancer with accuracy of 68% and larger T3/T4 lesions with accuracy of 73%.…”
Section: Resultsmentioning
confidence: 99%
“…They were able to identify mucosal cancer with accuracy of 68% and larger T3/T4 lesions with accuracy of 73%. 35 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, previous randomized controlled trials using AI computer-aided diagnosis alongside colonoscopies suggested a significantly higher detection rate for colorectal neoplasms than traditional colonoscopy [ 1 , 10 ]. Multiple studies also found that the training of a convolutional neural network to detect Barrett’s esophagus produced the same or higher accuracy rates than its human comparison [ 17 , 18 , 19 , 20 ]. With further trials to expand AI developments in endoscopy, the field of gastroenterology’s advances suggest that AI diagnostic models could be used as a supplemental tools alongside physicians’ judgments [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%